RAGAM EKSPRESI DAN INTERAKSI MANUSIA DENGAN AL-QUR’AN (DARI TEKSTUALIS, KONTEKSTUALIS, HINGGA PRAKTIS) - Faris Maulana Akbar (REVELATIA Jurnal Ilmu al-Qur`an dan Tafsir, 2022)
Al-Qur'an is a way of life for Muslims. As a way of life, the Qur'an is used as a reference in dealing with various problems of life, including the means to achieve the goals of human life. This means that the Qur'an is used as a tool to achieve this goal. Of course, as a tool, the Qur'an is only positioned as an object and humans are the subject. How do humans treat the Qur'an? This paper tries to explain the various expressions and interactions that occur between the Qur'an and humans in achieving their life goals. The results of this study found that there are at least there are at least three kinds of expressions and interactions that occur, namely: textualist, contextualist, and practical.